2010
DOI: 10.1007/s00406-010-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive therapy for treating schizophrenia: a chart review of patients from two catchment areas

Abstract: To examine disease and treatment characteristics of patients with schizophrenia treated with electroconvulsive therapy (ECT). We examined charts from 79 patients diagnosed with schizophrenia (n = 55), persistent delusional disorders (n = 7), and schizoaffective disorders (n = 17) between 2003 and 2008. We recorded age, sex, indication for ECT, number of ECT sessions, ECT series, outcome, maintenance ECT, use of antipsychotics, duration of illness, and duration of the current exacerbation. All patients were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 25 publications
4
41
0
3
Order By: Relevance
“…In a chart review by Kristensen, 18 patients received maintenance ECT in addition to antipsychotics. It was very effective in stabilizing the patients and reducing the length of hospital stay [52]. Another study has shown that continuous or maintenance ECT is safe and effective for chronically hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a chart review by Kristensen, 18 patients received maintenance ECT in addition to antipsychotics. It was very effective in stabilizing the patients and reducing the length of hospital stay [52]. Another study has shown that continuous or maintenance ECT is safe and effective for chronically hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies indicate that the use of continuation and maintenance ECT (C-ECT) is effective in terms of reducing the risk of relapse and readmission rates [31, 32]. Unfortunately, few prospective studies regarding maintenance in schizophrenia are available.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, Kristensen et al 10). evaluated the efficacy of ECT augmentation in 66 TRS patients, and 18 patients also received the maintenance ECT for periods ranging from 3 months to 12 years (mean, 2.2 years).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of C/M-ECT is reduced after the index ECT, lengthening the intervals between treatments from weekly to fortnightly, then monthly to prevent relapse (continuation) or recurrence (maintenance) 7,8). Most of previous studies on C/M-ECT for TRS schizophrenia were limited by the nature of the study design9) or the usage of qualitative outcome measures 10). Meanwhile, one study reported the effectiveness of maintenance ECT by retrospective analysis of 19 patients which showed that the mean duration of yearly hospitalization was decreased by 80% in chronic schizophrenia 11).…”
Section: Introductionmentioning
confidence: 99%